Práticas de multiletramentos no contexto escolar: investigação de uma abordagem pedagógica para o ensino de produção textual por meio de narrativas digitais - Cecchin, Anidene de Siqueira (2015)
Recent studies in Applied Linguistic (MOTTA-ROTH, 2006, 2008, 2009, 2010; SILVA, 2012; SILVA, PILATI, DIAS, 2010; FUZER, 2012, 2014 among others) show gaps in the process of learning and teaching of textual production in the Brazilian context.Therefore, it is essential to the school provide development of competences and abilities that enable the student to be part of the society when using verbal and nonverbal language to produce texts that embrace the use of different semiosis into the school practice. In this scenario, the text production task at school needs to be rethought to consider such needs, mainly as a way to create motivation and student‟s engagement in learning their mother tongue, in order to set up the act of writing as social practice (MOTTA-ROTH, 2006) which to communicate to life (HYLAND, 2007).Thus, in this study, we elaborated a proposal of a pedagogical approach in teaching Portuguese language (PL) through the use of digital narratives, based on the teaching and learning genre cycle (ROTHERY, 1996; ROSE; MARTIN, 2012), the concept of teaching approach proposed by Almeida Filho (1998) and the Digital Teaching Material Cycle (REIS; GOMES, 2014) with the purpose of promoting multiliteracies practices at school. In this way, an action research was developed in the public school context, in which didactic and pedagogical interventions were applied by the teacher-researcher and conducted to design a final proposal of digital storytelling online course, using the Moodle Platform. Four practical interventions were carried out with high school students from a public school of Santa Maria / RS.The data collected in the pilot pedagogical practices were obtained through two questionnaires (a diagnostic and evaluation one) applied during the course, through the analysis of four digital narratives produced by students and their responses to the proposed activities in the applied course and as through reflective journal produced by the teacher-researcher.The results show an encouragement of multiliteracies practices by the students involved in the process. By working with technologies associated with the study of language and digital storytelling production, the students developed school, digital and multimodal literacies in writing texts based on genres and making use of technological resources in the process of building knowledge at school. Moreover, it also became evident that the development of the teacher‟s digital literacy was essential to elaborate the digital teaching material used, as well as the academic literacy allowed the suitability of the teacher‟s writing in the scientific context. As the final product of this research, we can glimpse a proposal of teaching Portuguese language within a contextualized approach, integrating the use of technologies, that we call as Digital Storytelling Teaching and Learning Production‟s Cycle, based on six activities phases (Explore the narrative genres; Collaborative production of genres; Rewriting the genres; Independent Production of genres; Designing the Digital Storytelling; Sharing the Digital Storytelling). To sum up, we believe that this proposal may guide teachers in training and continuing education in their didactic and pedagogical practices for teaching digital storytelling in language classes.